The practice of hydrological restoration to rehabilitate abandoned shrimp ponds in Bunaken National Park, North Sulawesi, Indonesia - RIGNOLDA DJAMALUDDIN; BENJAMIN BROWN; ROY R. LEWIS III (Society for Indonesian Biodiversity, 2019)
Djamaluddin R, Brown B, Lewis III RR. 2019. The practice of hydrological restoration to rehabilitate abandoned shrimp ponds in Bunaken National Park, North Sulawesi, Indonesia. Biodiversitas 20: 160-170. The world has lost a large extent of mangroves, while rates of recovery of these ecosystems from natural re-growth and restoration are slow. We developed a hydrological restoration technique to investigate the importance of hydrological modification in mangrove restoration success. Ecological Mangrove Restoration was adopted to restore abandoned shrimp ponds at Tiwoho, Bunaken National Park, North Sulawesi. Hydrological modification resulted in the creation of various mangrove sub-habitat conditions. These conditions remained unstable within the first three years and became relatively stable after seven years. Tidal inundation and soil surface salinity appeared to be the major factors controlling mangrove establishment and growth. All natural recruits and planted trees grew faster and produced more propagules/fruits within a short period of time after the normal physical conditions achieved. The restored site was covered by approximately 91.3 % of vegetation with the same canopy species composition as the natural stands. The practiced hydrological restoration method was simple, cost-effective and can help other practitioners in improving their mangrove restoration techniques.